Symbolic and quantitative approaches to reasoning with uncertainty : 13th European Conference, ECSQARU 2015, Compiègne, France, July 15-17, 2015. Proceedings /: 13th European Conference, ECSQARU 2015, Compiègne, France, July 15-17, 2015. Proceedings. (2015) - Unknown
No abstract available